2021
DOI: 10.1002/ajim.23242
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory health and silicosis in artisanal mine workers in southern Brazil

Abstract: Background Artisanal and small‐scale mining (ASM) are an important source of employment in southern Brazil. Mining workers are frequently exposed to unhealthy work conditions which increase the risk of occupational diseases. In this study, we assessed the association of sociodemographic factors and the occupational history of artisanal mining workers with the risk of adverse respiratory outcomes. Methods The study was conducted with 258 artisanal mining workers in southern Brazil, who were exposed to dust (mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 22 publications
(55 reference statements)
0
18
1
Order By: Relevance
“…The prevalence of silicosis observed in our study was higher than the prevalence ratio of 3.08 reported in ASMs in southern Brazil [ 31 ]. However, our study employed convenience sampling, whereas the Brazil study employed random sampling.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…The prevalence of silicosis observed in our study was higher than the prevalence ratio of 3.08 reported in ASMs in southern Brazil [ 31 ]. However, our study employed convenience sampling, whereas the Brazil study employed random sampling.…”
Section: Discussioncontrasting
confidence: 90%
“…This is the first study to be conducted in Zimbabwe and in Africa among ASMs describing the burden of silicosis, silico-TB and TB. Apart from a study conducted in southern Brazil describing the prevalence of silicosis, we did not find comparable studies focusing on ASMs [ 31 ].…”
Section: Discussionmentioning
confidence: 79%
“…The mean duration of exposure to silica dust in this study was 9.82 ± 7.04 years. However, some studies have reported a high prevalence of respiratory symptoms in silica-exposed workers [ 38 , 39 , 40 ]. This discrepancy can be partially attributed to differences in the severity of exposure, duration of exposure, and some methodological flaws in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Souza et al. reported a high prevalence of respiratory symptoms in artisanal mine workers with a mean silica exposure of 1.6 mg/m 3 [ 38 ]. The severity and duration of exposure in their study were about 9 and 2.3 times higher than those in this study, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In developing countries such as India, the informal sectors of industry are not under statutory controls such as the 1948 Factory Act and thus remain unregulated [63]. This also applies to the artisanal and small-scale gold miners of Brazil, Myanmar and Zimbabwe [64][65][66], but is best exemplified by the agate industry in Gujarat, India. This industry is hundreds of years old and employs 20 000-50 000 workers [55].…”
Section: Sources Of Respirable Crystalline Silica Exposure and Epidem...mentioning
confidence: 99%